"Stark, necessary and not permanent": huts in the work of Paul Celan and J.H. Prynne - Thomas, Nicola (Wiley, 2016)
This article examines the motif of the hut in the work of Paul Celan and J. H. Prynne, as a metaphor for poetry which also mediates the relationship between poetry, language and place. Both Prynne and Celan’s use of the hut motif intersects with the role played by huts in work by Martin Heidegger, but this article demonstrates, through close reading of poems by Prynne and Celan, that both develop Heidegger’s understanding of the hut with reference to the ethical imperatives which underpin linguistic (and especially poetic) production.